2006
DOI: 10.1248/bpb.29.2126
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Neolignans Isolated from Piper regnellii (MIQ.) C. DC. var. pallescens (C. DC.) YUNCK against Trypanosoma cruzi

Abstract: The in vitro antiproliferative effects of 4 neolignans purified from the ethyl-acetate extract from leaves of Piper regnellii (MIQ.) C. DC. var. pallescens (C. DC.) YUNCK against Trypanosoma cruzi were investigated. These isolated compounds were identified through spectral analyses of UV, EI-MS, 1 H-, 13 C-NMR, H-H COSY, gNOE, HETCOR, and HMBC. The compounds eupomatenoid-5, eupomatenoid-6, and conocarpan showed considerable activity against epimastigote forms of T. cruzi, with 50% inhibition concentrations (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 17 publications
3
47
0
4
Order By: Relevance
“…In this context, several secondary metabolites of different structural patterns have proven active against T. cruzi (Saúde- Guimarães & Faria, 2007), and screening of plant extracts is a valid strategy being exploited to discover trypanocidal agents (Leite et al, 2001;Takahashi et al, 2002;Luize et al, 2006;Pizzolatti et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, several secondary metabolites of different structural patterns have proven active against T. cruzi (Saúde- Guimarães & Faria, 2007), and screening of plant extracts is a valid strategy being exploited to discover trypanocidal agents (Leite et al, 2001;Takahashi et al, 2002;Luize et al, 2006;Pizzolatti et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have demonstrated the therapeutic potential of compounds derived from natural sources. 16,[48][49] Several synthetic compounds have also shown trypanocidal activity. 50,51 Acanthoic acid (1) at 3 µmol L -1 (the lowest concentration tested) displayed a growth inhibition of parasites of 13.6%, while at the highest concentration (331 µmol L -1 ), over 90% of the cells were affected.…”
Section: Biological Studiesmentioning
confidence: 99%
“…The search of new drugs against leishmaniasis, potentially compounds and their derivatives have been described in the literature. [14][15][16] Neolignans are groups of compounds that show a wide range of biological effects including antifungal, [17][18][19] anti-schistosomal, [20][21][22][23] antiplasmodial, 24 trypanocidal, [25][26][27] antibacterial, 28 anti-PAF, 29,30 antipsychotic, 31 antioxidant, 32,33 activities, and biological activity against Escherichia coli,…”
Section: Introductionmentioning
confidence: 99%